Assessment of the potential risk of leaching pesticides in agricultural soils: study case Tibasosa, Boyacá, Colombia. Issue 11 (November 2021) - Navarro, Laura; Camacho, Ricardo; López, Julián E.; Saldarriaga, Juan F.
Abstract: Agricultural soils need monitoring systems to address pesticide risks for humans and the environment. The purpose of this paper was to obtain leaching risk maps of the pesticides imidacloprid, lambda-cyhalothrin, and chlorpyrifos in agricultural soil under an onion ( Allium cepa L.) crop in Tibasosa, Boyacá, Colombia. This was obtained by studying the soil types in the area, analyzing the behavior of pollutants in the soil profile, using a delay factor and an attenuation factor to finally include GIS allowing visualization of the areas of greater potential risk in the study area. Abstract : Leaching; Partition coefficient; Imidacloprid; Lambda-cyhalothrin; Chlorpyrifos; Potential risk.